(untitled) (Филологические заметки, 2019)
The article deals with the following themes: the conversion of poetic metaphysics into the system of the language games and structural transformations; the variability of the differences; the possibility of the analogy of the serial technics between a music and modern poetry; initial motives and metaphorical transferences of the senses; series of the poetic images with their movement, branching and interferences; metaphorical logic in the development of the serial recurrences; the serial Apnon; invariant result of the serial variations.